Comparative Analysis of 1965 and Indo-Pak 2025 Conflict - Azra Parveen Satti; Humair Naeem; Ahsan Khan Niazi; Haniya Afzal; Hayat Ahmad khan Jalali (`, 2025)
The main focus of this research paper is to comparatively analyze the Indo-Pakistan war of 1965 and 2025. Both the nations fought different wars on the Kashmir issue. 1965 war saw a significant tank battles between India and Pakistan. Similarly, 2025 war involved multi domain warfare including airstrikes, drone warfare, information and cyber operations. Similarly, conflict saw significant international diplomatic efforts. The main focus of this research is to analyze the warfare with both sides. Similarly, Pakistan economics situation during the conflicts of 1965 and 2025 also highlighted in this paper. Keywords: Operations, Economy, Military, Navy, Air Force, Diplomacy, Pakistan, India.